EXPLORING STUDENTS’ VIEWS ON THE USE OF PHOTOVOICE FOR SELF-ASSESSMENT AND PEER FEEDBACK IN AN EFL CONTEXT [EKSPLORASI PANDANGAN SISWA TERHADAP PEMANFAATAN PHOTOVOICE DALAM PENILAIAN DIRI DAN UMPAN BALIK REKAN DALAM KONTEKS EFL] - Priscilla Maria Assis Hornay; Maria Goreti Djehatu; Floribertha Lake (Polyglot: Jurnal Ilmiah)
The use of self-assessment and peer feedback in language learning has gained significant attention due to its potential to foster learner autonomy and improve academic outcomes. However, despite the growing interest, there is limited research on the integration of creative, visual methods, such as photovoice, into these practices, particularly in the context of English as a Foreign Language (EFL) learning. This study aims to explore students' perceptions of using photovoice as a tool for self-assessment and peer feedback, focusing on how this approach can promote self-reflection, critical thinking, and constructive peer interaction. Data was collected from a group of EFL students using a questionnaire, with responses analyzed using descriptive statistics. The findings reveal that the majority of students feel confident in conducting self-assessment, though comfort with peer feedback is more varied, with some expressing uncertainty. Additionally, photovoice is perceived positively by students, who identify it as an effective means of enhancing reflective skills and self-expression. The study concludes that photovoice offers a promising approach to engaging students in self-assessment and peer feedback, making learning more interactive and reflective. The findings suggest that integrating visual methods into EFL classrooms can foster deeper learner engagement and support the development of evaluative judgment. Future research should investigate the broader applicability of photovoice in diverse EFL contexts and its impact on student autonomy and collaborative learning.